Pelatihan Sablon Baju Digital Karang Taruna Pemuda Kampung Bagan Kota Batam Sebagai Fondasi Pertumbuhan Ekonomi dan Keberlanjutan Budaya - Hutabri, Ellbert; Satria, Robby; Elisa, Erlin; Fajrin, Alfannisa Annurrallah (PUAN INDONESIA, 2024)
Kampung Bagan, an old Malay village on the coast of Tanjung Piayu, Batam City, has great cultural and economic potential but faces challenges in maintaining its cultural identity and competitiveness in the era of globalization. The youth of Kampung Bagan, most of whom work as factory workers, fishermen and traders, have creativity that has not yet been fully explored. Karang Taruna Kampung Bagan plays an important role in social and cultural activities. To empower youth, digital clothing screen printing training was carried out which integrated Malay cultural motifs into clothing designs. This training aims to improve skills, empower the local economy, preserve culture, and encourage creativity and innovation. This program involves team formation, needs analysis, and impact evaluation using guided training methods. The results show an increase in youth skills and income as well as an increase in community solidarity. Challenges such as limited resources and participation need to overcome poverty programs. It is hoped that the revitalization of the creativity of the Kampung Bagan Youth Youth Organization through digital clothing screen printing training will be able to provide a solid foundation for economic growth and cultural prosperity, making youth better prepared to face global challenges and increasing community competitiveness.